Beef cattle welfare: the role of Integrated Systems in animal adaptation and productivity - Martin, Daniela Maria; Moraes, Renata Franciéli; Ruthes, Barbara Elis Santos; de Oliveira, Leandro Bittencourt; de Moraes, Anibal (Frontiers in Ethology, 2025)
IntroductionThe domestication of cattle has shaped their adaptation to livestock environments, although management conditions often limit their welfare and productivity. This study investigated whether integrated livestock–forestry (LF) systems improve the behavior, welfare, and productivity of beef cattle compared to conventional livestock (L) systems.MethodsEighteen Angus steers were monitored for ten consecutive months under continuous grazing. Welfare indicators were assessed according to the Welfare Quality® protocol, with adaptations for grazing conditions.ResultsBoth systems ensured adequate feeding, health, and rest conditions. However, animals in the LF system performed better in thermal comfort and human–animal interaction. Specifically, LF cattle had a 2.5 °C lower body surface temperature, a 63% smaller flight zone, and an 85% lower reactivity score than cattle in the L system. Average daily weight gain and body condition score did not differ between systems.DiscussionIntegrated livestock–forestry systems enhanced adaptive behaviors and animal comfort without compromising productivity. These findings highlight LF systems as a sustainable approach to balancing animal welfare with production efficiency.